Strategic Management and Business Policy: Globalization, Innovation and Sustainability, Global Edition - Wheelen, Thomas L.; Hunger, J. David; Hoffman, Alan N.; Bamford, Charles E. (Pearson International Content, 2023)
Picking up where popular previous editions left off, Concepts in Strategic Management and Business Policy further sharpens and modernizes this text’s approach. It teaches strategy with an emphasis on globalization, innovation and sustainability. And teaches you the strategic concepts you should know as you face the issues that all organizations must build upon to push their businesses forward. With new cases, vignettes, examples and statistics in the 16th Edition, you get an extraordinarily well-researched and practically crafted lesson.